The education and training of performing musicians from Hong Kong, South Korea and Singapore : a comparative study - Tan, Soon Leng. (2009)
The topic of this research is The Education and Training of Performing Musicians from Hong Kong, South Korea and Singapore - A Comparative Study'. The purpose of this research was to analyse the nature of training and the education of a sample group of performing musicians from these countries, in order to assess the effectiveness of their training and to make a detailed study of some outstanding music institutions in the home regions as well as overseas. It was also to make recommendations for music training and education in Singapore.